Pengembangan Wisata Cemoro Barong di Tulungagung - Sulistya, Wyne Rahma; Supranoto, Supranoto; Suryawati, Dina (Universitas Moch. Sroedji, 2024)
This research aims to describe the role of the village government in developing Cemoro Barong Tourism in Tapan Village, Kedungwaru District, Tulungagung Regency. Tapan Village has local potential that can be utilized and developed for tourism. Cemoro Barong Tourism is one of the tourist attractions owned by Tapan Village which is a new tourist attraction and has the potential to be developed into a tourist event. Because tourism is still new, it really needs development and also the role of related parties in carrying out promotions so that it can be known by people outside the village. This tourism development has the opportunity to carry out village development, community development and community empowerment. Therefore, the role of village government is very important in its implementation. This research is a qualitative descriptive study using data collection techniques through observation, interviews and documentation. The results of this research show the role of the Village Government in developing Cemoro Barong Tourism in Tapan Village, Kedungwaru District, Tulungagung Regency, namely 1) As a Regulator, making regulations whose aim is to prepare directions for organizing tourism development activities. As a regulator, the Tapan Village government makes regulations that are used as a reference in the tourism development process. These rules include visitor ticket fees, parking fees and a prohibition on carrying sharp objects. 2) as a dynamist, the Tapan Village government encourages community participation by conducting tourism destination management training held at the village hall. 3) as a facilitator, providing funding or capital that is used for the tourism development process by building facilities in the form of facilities and infrastructure which will later support the attraction of visitors to visit. 4) as a catalyst, the Tapan Village government accelerated the process of developing Cemoro Barong tourism by promoting tourism by utilizing social media accounts owned by the village such as Instagram and YouTube.